â€œTeaching is Godâ€™s Callingâ€: Teachersâ€™ Beliefs and Professional Identity at Ten Christian Schools in Indonesia - Yumarnamto, Mateus; Prijambodo, Vincentius Luluk (International Journal of Education, 2020)
Teachersâ€™ beliefs and their roles in the classroom may change over time as they are more informed about the profession from their own experiences, from their colleagues, and from their continuing education. In this study we investigated teachersâ€™ beliefs and roles at 10 Christian schools in East Java, Indonesia to see how their beliefs influence their professional identity development. The data were collected from 107 teachers who participated in semi-structured interviews and who wrote reflective essays as a part of their career development program. The data were analyzed in the framework of narrative inquiry to see the emergent themes. The findings suggest that the most salient beliefs among the participating teachers are the beliefs which are based on their Christian affiliation. These salient beliefs and Christian identity of the teachers could enhance their positive image as teachers and could motivate them to be better teachers. However, the salient religious identity may also be able to be hindrance for teacher agency to solve problems in their practices as the beliefs can be the shielding for their reluctance to change.